2015
DOI: 10.4028/www.scientific.net/amm.758.143
|View full text |Cite
|
Sign up to set email alerts
|

CFD Study on the Ventilation System and Shape Configuration of Underground Car Park in Case of Fire

Abstract: Fire in a typical car park is capable to induce large Heat Release Rate. The heat release rate in car park can be ranged from 500 kW to 20 MW depends on the ventilation condition of the car - park and the car itself. When fire occurs in poor ventilated car, i.e. the window is closed, fire will immediately burn out. Otherwise, fire will rapidly spreads and consume adjacent car. This condition can result in wide spread of fire involving all of the available car in the parking lot considering the availability of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…A lot of fire simulations have been performed by other researchers such as [4,12,13,[15][16][17][18][19][20][21][22][23][24] due to the reliability of FDS.…”
Section: Methodsmentioning
confidence: 99%
“…A lot of fire simulations have been performed by other researchers such as [4,12,13,[15][16][17][18][19][20][21][22][23][24] due to the reliability of FDS.…”
Section: Methodsmentioning
confidence: 99%
“…In literature, different car fire source treatments were implemented for car fire smoke simulations. Santoso [13] set the fire source of 10MW steady state HRR with soot and CO yield of 0.01 and 0.1 respectively. Eimermann [2] recommends soot yield of 0.1 to 0.2 and He 20 to 40J /kg, which leads to soot production of minimum of 5.8kg to 68kg in 10 to 20 minutes.…”
Section: Fire Smoke Source For Car Park Numerical Simulationsmentioning
confidence: 99%
“…Many smoke control systems design validation studies have been published recently using CFD simulations. Santoso [13] studied the effect of horizontal ventilation system and its thrust direction on the spread of smoke, as well as, the impact of additional building structure on smoke flow pattern and extraction effectiveness. X. Deckers [1] study presented a full-scale fire and smoke CFD simulation and showed the effect of structural beams on the spread of smoke.…”
Section: Introductionmentioning
confidence: 99%
“…The numerical simulation was performed in the (Autodesk CFD, Ansys, SimScale) modelling environment, and the purpose of the study is to determine the behaviour of a ventilation system with impulse fans operating in an underground car park, to identify possible methods of streamlining the system. [2], [3], [6], [13], [17], [19] For the analysis of the scenarios considered in the present study, a P2 type underground parking lot with a capacity of 250 vehicles was used. The car park has a single level located in the basement of an office building, with an area of 6750 m 2 and a height of 3.5 m, resulting in a total volume of 23625 m 3 .…”
Section: Numerical Modellingmentioning
confidence: 99%